Qualitative evaluation of a form for standardized information exchange between orthopedic surgeons and occupational physicians - van Staa Anne; Burdorf Alex; Faber Elske; Miedema Harald S; Verhaar Jan AN (BMC, 2006)
Abstract Background Both occupational physicians and orthopedic surgeons can be involved in the management of work relevant musculoskeletal disorders. These physicians hardly communicate with each other and this might lead to different advices to the patient. Therefore, we evaluated a standardized information exchange form for the exchange of relevant information between the orthopedic surgeon and the occupational physician. The main goals of this qualitative study are to evaluate whether the form improved information exchange, whether the form gave relevant information, and to generate ideas to further improve this information exchange. Methods The information exchange form was developed in two consensus meetings with five orthopedic surgeons and five occupational physicians. To evaluate the information exchange form, a qualitative evaluation was set up. Structured telephone interviews were undertaken with the patients, interviews with the physicians were face-to-face and semi-structured, based on a topic list. These interviews were recorded and literally transcribed. Each interview was analyzed separately in Atlas-Ti. Results The form was used for 8 patients, 7 patients agreed to participate in the qualitative evaluation. All three orthopedic surgeons involved and three of the six involved occupational physicians agreed to be interviewed. The form was transferred to 4 occupational physicians, the other 3 patients recovered before they visited the occupational physician. The information on the form was regarded to be useful. All orthopedic surgeons agreed that the occupational physician should take the initiative. Most physicians felt that the form should not be filled out for each patient visiting an orthopedic surgeon, but only for those patients who do not recover as expected. Orthopedic surgeons suggested that a copy of the medical information provided to the general practitioner could also be provided to occupational physicians. Conclusion The information exchange form was regarded to be useful and could be used in practice. The occupational physician should take the initiative for using this form and most physicians felt the information should only be exchanged for patients who do not recover as expected. That means that the advantage of giving information early in the treatment is lost.